MAMAK IN NOVEL PERSIDEN BY WISRAN HADI PSYCHO-SOCIALCRISIS ERIKSON ANALYSIS (MAMAK DALAM NOVEL PERSIDEN KARYA WISRAN HADI KAJIAN PSYCHO-SOCIALCRISIS ERIKSON) - Samsiarni, Samsiarni (Universitas PGRI Sumatera Barat, 2019)
This study aims to look at the problems represented by Mamak's character in the Novel Persiden By Wisran Hadi using Erikson's psycho-crisis theory. The mamak figure in this novel experienced problems between having to play the role of mamak and the fact that mamak did not have the same power as before. This research uses descriptive method with content analysis approach. The results of the study show that Novel Persiden By Wisran Hadi shows the figures of the mamak Malati. Thirdly, Mamak Malati, Pa Tandang, Pa Rarau and Pa Mikie are in an uncertainty between not wanting to be involved in the problem and having to be involved because of their roles and functions as mamak. This causes Minangkabau men to be in the dilemma of being individuals who are only involved with their families or mamak who must be role models for their nephews.